TSH cut off point based on depression in hypothyroid patients - Talaei, A (BMC Psychiatry, 2017)
BACKGROUND: The prevalence of depressive symptoms in hypothyroidism is high. Considering that hypothyroidism and depression share some clinical features, some researchers use the “brain hypothyroidism” hypothesis to explain the pathogenesis of depression. We aimed to detect a new TSH cut-off value in hypothyroidism based on depression symptoms. METHODS: A cross-sectional study was conducted on hypothyroid patients referred to endocrine clinics. Individuals who had developed euthyroid state under treatment with levothyroxine with TSH levels of 0.5–5 MIU/L with no need for dosage change were included in the study. After comprehensive history taking, laboratory tests including TSH, T4 and T3 were performed. Beck depression questionnaire was completed for all patients by trained interviewers. TSH cut-off values based on depression was determined by Roc Curve analysis. RESULTS: The participants were 174 hypothyroid patients (Female; 116: 66.7%, Male; 58: 33.3%) with mean age 45.5 ± 11.7 (19–68) years old. Based on Beck depression test, scores less than 10 was considered healthy and more than 10 were considered depressed. According to Roc curve analysis, the optimal cut- off value of TSH was 2.5 MIU/L with 89.66% sensitivity. The optimal TSH cut- off based on severe depression was 4 MIU/L. CONCLUSION: The present study suggests that a clinically helpful TSH cut-off value for hypothyroidism should be based on associated symptoms, not just in population studies. Based on the assessment of depression, our study concludes that a TSH cutofff value of 2.5 MIU/L is optimal.